ISO 9001:2015 adoption: A multi-country empirical research - Fonseca, Luís (2019)
This paper aims at identifying obstacles, benefits, leading practices and lessons learned in the transition/certification of the revised standard for quality management systems ISO 9001:2015 for organizations in various sectors, countries and spanning a range of sizes. Design/methodology/approach: Based on literature review and inputs from experts in management systems certification, a quantitative survey was launched in Portugal, Romania, Switzerland, and Turkey in April 2018, addressed at quality and organizational managers and CEOs from ISO 9001:2015-certified organizations by certification bodies partners of the leading International Quality Network (IQNet). The answers were collected anonymously through an automated online database, until the end of April 2018. The overall response rate was 3.1%, encompassing 222 organizations already certified according to ISO 9001:2015. The surveyed organizations reported significant benefits from ISO 9001:2015 implementation. Only 3.9% of the respondents considered the 3-year transition period (from September 15, 2015, to September 15, 2018) as too short. The respondents’ organizations attended ISO 9001:2015 training and seminars, and collected information from websites, newsletters, books and interpretation guides and directly from certification bodies. Some (29.8%) relied on their own internal resources for the transition processes, while external consultants supported 22.7%. The respondents considered the adoption of riskbased thinking the major difficulty to be overcome, but simultaneously as the major benefit to be realized. The alignment with other management systems, the increased top management commitment, the identification of risks and opportunities and the knowledge management were also reported as significant benefits. The initial timing when organizations started working on the transition process and the activities carried out seem to differ between countries, while the adjustments performed to the existing management systems seem to differ by sector and size of the organization. The benefits attained by the organizations vary according to the perception regarding the information resources made available and organizations should be aware of the advantages of early planning. The organizations that rated the benefits of ISO 9001:2015 adoption higher considered the information resources as adequate and started working with ISO 9001:2015 at an earlier stage, while those that rated the benefits lower stated that the information resources were made available too late. The organizations that successfully managed the ISO 9001:2015 transition/certification process were the ones that attended ISO 9001:2015 training courses and seminars and got useful information from their certification body.